2022
DOI: 10.3389/fphar.2022.925514
|View full text |Cite
|
Sign up to set email alerts
|

Research progress on classical traditional chinese medicine formula xiaoyaosan in the treatment of depression

Abstract: Depression is an emotional disorder that is problematic in psychiatry owing to its unclear etiology and unknown pathogenesis. Traditional Chinese medicine formulations such as Xiaoyaosan have been widely used throughout history to treat depression. In this review, we have focused on recent evidences elucidating the links between Xiaoyaosan and the treatment of depression. Data from animal and clinical studies, focusing on the pharmacological mechanisms, clinical applications, and effective materials that form … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 123 publications
0
11
0
Order By: Relevance
“…Manipulation of gut microbes is considered a potential treatment for depression [ 32 ]. As a botanical formulation widely used in Asia and Europe, XYS contains a variety of active substances and is considered to have prebiotic-like properties [ 20 ]. In the current study, XYS, a potential antidepressant drug, was used to explore the role of gut microbiota in the treatment of depression and the specific mechanisms underlying the interaction between gut microbes and the CNS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Manipulation of gut microbes is considered a potential treatment for depression [ 32 ]. As a botanical formulation widely used in Asia and Europe, XYS contains a variety of active substances and is considered to have prebiotic-like properties [ 20 ]. In the current study, XYS, a potential antidepressant drug, was used to explore the role of gut microbiota in the treatment of depression and the specific mechanisms underlying the interaction between gut microbes and the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…F.A. Wolf), Glycyrrhiza glabra L., Mentha canadensis L., and Zingiber officinale Roscoe in a 5:5:5:5:5:4:1:5 ratio [ 19 , 20 ]. XYS has a long history as a traditional treatment for emotional disorders in Asian countries, including China, Japan, and South Korea, and has also been used for traditional application as a health food or herbal medicine in European counties, including the UK, the Netherlands, and Germany for > 30 years [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, few reports have shown that Xiaoyaosan granules induce side effects via FXR activation. It has been used to treat mental illnesses for centuries without obvious adverse effect [46] . Previous reports have shown that Xiaoyaosan granules ameliorate glucocorticoid-induced hepatic steatosis by decreasing the translocation of GR into the nucleus [18] .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this result should be carefully interpreted due to concerns about publication bias and poor clinical research quality ( 32 ). The potential mechanisms of Xiao Yan Wan could involve the modulation of monoamine neurotransmitters, and regulation of the HPA axis, but more solid research is required ( 33 ).…”
Section: Efficiency and Safety Of Chm For Mddmentioning
confidence: 99%